Inclusive Education Management Strategies Utilizing Virtual Reality Technology for Students with Special Needs - Lulu Khairunnisa; Akhmad Ramli (UIN Siber Syekh Nurjati Cirebon, 2025)
Inclusive education management strategies based on Virtual Reality (VR) technology represent an innovative approach to supporting the learning of students with special needs. This study aims to analyze how educational management strategies can optimize the use of Virtual Reality technology in creating safe, interactive, and adaptive learning environments. The methodology that used is descriptive qualitative literature research. The review process was conducted systematically, beginning with topic identification, followed by source selection, thematic analysis, and culminating in conceptual synthesis. The findings indicate that effective inclusive education management must encompass five key pillars: adaptive curriculum planning, teacher training, infrastructure provision, learning evaluation, and cross-sector collaboration. Virtual Reality technology has proven to significantly enhance learning motivation, conceptual understanding, emotional regulation, and active participation among students with special needs. Despite challenges such as limited budgets, digital gaps, and resistance to change, responsive and collaborative management strategies are essential to the successful transformation of inclusive education through technology.